THE IMPACT OF CUSTOMER RELATIONSHIP MANAGEMENT ON CUSTOMER SATISFACTION AND RETENTION: THE CASE LEBANON - Annan, Saher Al; Haidoura, Hani; Shatila, Khodor; Alozian, Marina (International Journal of Psychosocial Rehabilitation, 2020)
For various reasons, the execution of a CRM system is likely to have an impact on customer satisfaction and customer information. Similarly, the implementation of a CRM approach is likely to affect customer satisfaction and customer knowledge. CRM ensures customers return home with a smile and improves the relationship between the organization and its customers. Such activities strengthen the bond between sales representatives and customers. The research implemented the quantitative methodology throughout distributing the questionnaire over 100 bank customers. The data was treated using the SPSS statistical tool throughout descriptive and inferential statistics. The research findings proved that there is a direct relationship between customer loyalty and customer satisfaction and CRM technology, the higher the CRM technology had been implemented the higher the customer satisfaction rate will be